Risk and Social Interactions in the Adoption of Improved Dairy Breeds by Smallholder Farmers in Kenya - Kimani, David (European Scientific Journal, ESJ, 2017)
This study investigates the role of production risk and social interaction in the adoption of improved dairy breeds by smallholder farmers in Kenya. In agricultural production outputs are uncertain and they may turn out to be favorable or unfavorable. Therefore, farmers may not always get what they expect to produce. Deviation from expected output constitutes production risk. This form of risk is said to hinder the adoption of yield increasing technologies. Farmers rarely have complete information about the performance of new agricultural technologies. Lack of perfect information about the performance of new technologies may as well hinder adoption. To fill the information gap farmers seek to acquire information through formal and informal sources. Informal sources include social interations with peers and neighbors. Flexible moments method is used to derive production risk variables. While mean values of selected variables of a reference group defined at village level are used as proxies for social interactions. The study applies three different methods, probit, two-stage instrumental variable, and Control function on cross-sectional data collected from a sample of 373 smallholder farmers to evaluate role of risk and social interactions in the adoption of improved dairy breeds. The finding shows that endogenous social Interactions as measure by proportion of improved breeds’ adopters in a reference group have positive and significant effect on adoption of improved dairy breeds. Production risk as measured by variance and skewness of milk output is found to have negative and significant effects of adoption of improved dairy breeds.